Clickable amino acid tuned self-assembly of a nucleus-selective multi-component nanoplatform for synergistic cancer therapy. Issue 24 (21st May 2021) - Yang, Lan; He, Xiao; Zeng, Zhiying; Tang, Jiakun; Qi, Dongmei; Ma, Huijie; Chen, Hui; Ning, Xinghai; Feng, Xuli
Abstract : A highly efficient nucleus-targeted multi-drug delivery nanoplatform based on clickable amino acid tuned self-assembly of chlorin e6 and doxorubicin has been prepared for enhanced photodynamic therapy and chemotherapy. Abstract : Nucleus-targeted therapy holds great promise in cancer treatment; however, a lack of effective nucleus-specific delivery significantly limits its application potential. Here, we report a nucleus-targeted synergistic chemo-photodynamic therapy based on the self-assembly of chlorin e6 (Ce6) and doxorubicin (DOX) tuned by clickable dibenzocyclooctyne (DIBO) functionalized lysine (D-K ) and subsequent reaction with crosslinkers. The assembled nanodrugs with high loading efficiency and long-term stability show enhanced cellular uptake and accumulation in the nucleus, resulting in greatly improved in vitro and in vivo chemo-photodynamic efficacy. Notably, D-K can promote the rapid self-assembly of Ce6 and DOX in aqueous solution, avoiding the introduction of organic solvents or tedious preparations. In addition, the introduction of the DIBO group can effectively expand the types of self-assembly material and enhance the self-assembly behaviour through a copper-free click reaction. Therefore, we present an effective nucleus-targeted combination drug delivery strategy, which has great potential in the treatment of many diseases.